Trends in Global, Regional, and National Burden and Quality of Care Index for Liver Cancer by Cause from Global Burden of Disease 1990‐2019 - Seyyed‐Hadi Ghamari; Moein Yoosefi; Mohsen Abbasi‐Kangevari; Mohammad‐Reza Malekpour; Sahar Saeedi Moghaddam; Sarvenaz Shahin; Zahra Esfahani; Sogol Koolaji; Parnian Shobeiri; Aydin Ghaffari; Hanye Sohrabi; Ameneh Kazemi; et al. (Hepatology Communications, 2022)
Despite the tremendous burden of liver cancer and its underlying causes on humankind, there appear to be heterogeneities in coping approaches. The objective of this study was to compare the burden and the quality‐of‐care of liver cancer by causes among different countries and regions in both sexes and various age groups 1990‐2019. Data of liver cancer and underlying causes, including hepatitis B virus (HBV), hepatitis C virus (HCV), alcohol use, nonalcoholic steatohepatitis (NASH), and other causes were obtained from the Global Burden of Diseases 2019. Incidence, prevalence, death, and disability‐adjusted life‐years (DALYs) were assessed. Principal component analysis was used to combine age‐standardized mortality‐to‐incidence ratio, DALY‐to‐prevalence ratio, prevalence‐to‐incidence ratio, and years of life lost–to–years lived with disability into a single proxy named Quality of Care Index (QCI). Globally, the age‐standardized incidence, DALYs, and death rates decreased from 1990 to 2019, while the QCI scores increased by 68.5%. The QCI score of liver cancer was from as high as 83.3 in high Sociodemographic Index (SDI) countries to values as low as 26.4 in low SDI countries in 2019. Japan had the highest QCI score (QCI = 100). The age‐standardized death rates of liver cancer due to all underlying causes were decreasing during the past 30 years, with the most decrease for HBV. Consistently, the global QCI scores of liver cancer due to HBV, HCV, alcohol use, NASH, and other causes reached 53.5, 61.8, 54.3, 52.9, and 63.7, respectively, in 2019. Conclusion: Although the trends in burden are decreasing and the QCI improved from 1990 to 2019 globally, there is a wide gap between countries. Given the inequities in health care quality, there is an urgent need to address discrimination and bridge the gap.